Numerical Analysis for the Oxidation of Phenol with TiO2 in Wastewater Photocatalytic Reactors - Maddah, H. A. (Engineering, Technology & Applied Science Research, 2018)
Phenolic compounds in wastewater (even at low levels) are found to be quite toxic to humans due to their carcinogenic effects. Photocatalysis has been widely studied for the removal of phenol from industrial wastewater. In this study, photocatalytic oxidation of phenol, under UV irradiation in the presence of TiO2, has been numerically investigated. Phenol mass balance and forward finite difference method (explicit) along with various assumed/calculated parameters, from previous works, were used to numerically plot phenol concertation profiles in water with different initial phenol concentrations. Phenol compounds were observed to be totally oxidized at the bottom of the reactor and the maximum conversion rates occur near the reactor walls. It was found that higher irradiation times increase phenol oxidation rates due to higher water hydrolysis. Oxidation rate of phenol (consumption) increases with the increase in initial phenol concentration.